Governance structures in smallholder pig value chains in Uganda: constraints and opportunities for upgrading - Ouma, Emily A.; Ochieng, J.; Dione, Michel M.; Pezo, Danilo A. (Brill, 2017)
This paper analyses governance structures in Uganda’s smallholder pig value chains by applying the New Institutional Economics framework. It utilises cross sectional and qualitative survey data from randomly selected pig value chain actors in 4 districts. A multinomial logit model is applied to assess the determinants of vertical integration among pig traders. The findings indicate that most relationships at the pig production node of the value chain are based on spot market governance structures supported by personal relationships and trust. Live pig traders are mostly vertically integrated. High integration levels of the pig traders are positively influenced by access to market information, value of investments in the value chain, and dedicated asset specificity in terms of backyard slaughter premises. Upgrading opportunities in the value chain in the form of value addition strategies, policy implementation and promotion of business models that link producer organisations to quality inputs and service suppliers through contractual arrangements are identified.